-4(2x-7)=3(52-4x)
We move all terms to the left:
-4(2x-7)-(3(52-4x))=0
We add all the numbers together, and all the variables
-4(2x-7)-(3(-4x+52))=0
We multiply parentheses
-8x-(3(-4x+52))+28=0
We calculate terms in parentheses: -(3(-4x+52)), so:
3(-4x+52)
We multiply parentheses
-12x+156
Back to the equation:
-(-12x+156)
We get rid of parentheses
-8x+12x-156+28=0
We add all the numbers together, and all the variables
4x-128=0
We move all terms containing x to the left, all other terms to the right
4x=128
x=128/4
x=32